Pengaruh Operating Capacity Dan Sales Growth Terhadap Financial Distress Pada Pt Bentoel Internasional Investama TBK - natalia, indah; Huda, Nurul (Journal MISSY (Management and Business Strategy), 2023)
This study aims to analyze the effect of operating capacity and sales growth on financial distress at PT Bentoel Internasional Investama Tbk. This type of research is associative which aims to determine the influence or relationship between two or more variables. The analytical tools used are classical assumption analysis, normality analysis, autocorrelation analysis, multiple linear regression, t test and f test (SPSS Version 16). The results of this study indicate that operating capacity does not affect financial distress and sales growth does not affect financial distress.